(untitled) (Scientific journal of the Fergana State University, 2023)
This article illustrates the historical foundations of the genre of story, the stages of its development and the research conducted in this field in the world and Uzbek literature. Changes in the canons of the genre of story, its architectonics, specific features, the tendency to update the nature of its form and content, the factors that contributed to the development of short stories are scientifically covered. The influence of the stories of world literature on the development of Uzbek story writing and the innovations in this sphere of the independence period are studied.